Optimizing Rice Plants (Oryza sativa L.) Growth and Yield in Various Planting Systems by Providing Paclobutrazol Concentration - Maya Novita; Agus Sulistyono; Ida Retno Moeljani (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2025)
Rice (Oryza sativa L.) is the primary staple food crop and a strategic source of carbohydrates for the Indonesian population. In recent years, rice production has declined at both national and local levels due to climate change, land limitations, and pest disturbances. This condition highlights the urgent need for research to develop more efficient and sustainable rice cultivation strategies. This study aimed to determine the interactive effects of planting systems and Paclobutrazol concentrations on the growth and yield of the rice variety Inpari 32. The research was conducted in Ngraho District, Bojonegoro Regency, East Java, using a Split Plot Design with two factors: planting systems (Tegel/traditional, SRI, Legowo 2:1, and modified Legowo) and Paclobutrazol concentrations (0, 600, 700, and 800 ppm). Observed parameters included plant growth and yield components. The results revealed significant interactions between planting systems and Paclobutrazol concentrations on several parameters, including the number of panicles, panicle length, and grain weight per cluster. The best results were obtained with the modified Legowo system combined with 600 ppm Paclobutrazol, which produced yields exceeding 6 tons per hectare. This combination is recommended as an effective cultivation strategy to enhance rice productivity and support sustainable national food security.